Caregiving in U.S. Gulf States During Natural Disasters and COVID-19. (October 2022) - Boucher, Nathan A.; McKenna, Kevin; Dombeck, Carrie B.; Clark, Amy G.; Wang, Ke; Olsen, Jennifer M.; Shepherd-Banigan, Megan
Objectives: To ascertain common experiences and needs of a diverse group of caregivers challenged by hurricanes/floods and COVID-19. Methods: In-depth interviews with unpaid caregivers in U.S. Southeast/Gulf Coast states who had experienced caregiving during a natural disaster and during COVID-19. Results: Caregivers report challenges including daily living disruption, altered social supports, complicated health management, additional disaster planning, and emotional/financial impacts. Caregivers suggested helpful resources, policy options, and preparatory tools at individual, local, and health system levels to mediate discontinuity. Conclusions: Our data describe combined caregiver experiences of hurricanes/floods and the pandemic. Caregivers experience unique burdens related to care recipient diagnosis, location, and veteran status. Access to community supports varies as they manage the tasks required for care recipients' health and safety. Our findings indicate the need for public health reinforcement of caregiving though caregiver pre-planning and targeted support. Bolstering understanding of communities' caregiving capacity though first responder trainings and caregiver registries may enhance health and safety.